2017
DOI: 10.1002/lary.26612
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for elevated intracranial pressure improves success rate after repair of spontaneous cerebrospinal fluid leaks

Abstract: 4. Laryngoscope, 127:2011-2016, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 69 publications
(100 reference statements)
2
89
1
2
Order By: Relevance
“…Spontaneous CSF leaks have a higher postoperative recurrence rate than other types of CSF leaks, the cause of which some authors presume to be the elevated ICPs . A recent study showed that in patients undergoing operative repair of CSF leak, postoperative acetazolamide decreased recurrence rate by 11% . In our clinical experience, a subset of patients with spontaneous CSF leaks pretreated with acetazolamide have not required surgery.…”
mentioning
confidence: 56%
“…Spontaneous CSF leaks have a higher postoperative recurrence rate than other types of CSF leaks, the cause of which some authors presume to be the elevated ICPs . A recent study showed that in patients undergoing operative repair of CSF leak, postoperative acetazolamide decreased recurrence rate by 11% . In our clinical experience, a subset of patients with spontaneous CSF leaks pretreated with acetazolamide have not required surgery.…”
mentioning
confidence: 56%
“…Teachey et al performed a systemic review comparing successful closure of anterior skull base CSF fistula between patients who had active versus no management of elevated ICP. The success rate for the actively managed group was 92.8% compared to 81.9% for the group that did not undergo management of elevated ICP ( P < .001) . Although there are no comparable studies for lateral skull base CSF fistula, it could be assumed treatment of elevated ICP will result in fewer recurrences.…”
Section: Discussionmentioning
confidence: 94%
“…The success rate for the actively managed group was 92.8% compared to 81.9% for the group that did not undergo management of elevated ICP (P <.001). 38 Although there are no comparable studies for lateral skull base CSF fistula, it could be assumed treatment of elevated ICP will result in fewer recurrences.…”
Section: Long-term Management Of Elevate Intracranial Pressurementioning
confidence: 99%
“…Of note, other mechanisms may be involved, such as transverse sinus stenosis . In anterior skull‐base CSF leak, it has been shown that the management of elevated ICP improved the success rate of surgical closure of the leak . This seems to be different in temporal bone CSF leak: the relatively high success rates obtained with a strategy that did not include information on ICP suggest that the duraplasty may be more reliable in temporal bone than in anterior skull‐base defects.…”
Section: Discussionmentioning
confidence: 99%